The human blend eaudiobook - Foster, Alan Dean (Tipping Point Trilogy, 2010)
The Human Blend is a science fiction adventure centered around a group of thieves living in a future where physical alterations and enhancements are an everyday common occurrence. If you could take on a body with any features you wanted, what would it look like? And what would you do with them—human or otherwise?